Multinationals vs. cooperatives: The income and efficiency effects of supply chain governance in India - Vandeplas, Anneleen; Minten, Bart; Swinnen, Johan (Wiley, 2013)
The impact of multinational firms on the domestic agricultural sector in developing countries is controversial, in particular in India. Relying on a unique set of household‐level data from the state of Punjab, we study the biggest dairy company in the world (Nestlé) in India and compare its vertical spillover effects on upstream suppliers to other market channels (informal sector and cooperatives). We find that farmers that supply informal channels are less efficient and earn lower profits per dairy animal than farmers supplying the cooperative and the multinational sector. Furthermore, we find that farmers using the multinational channel are more efficient than farmers in the cooperative channel, but equally profitable. Hence, we do not find that supplying the cooperative channel is more beneficial for local dairy farmers than supplying the multinational channel. Overall, however, dairy productivity and profitability levels are still dramatically low, with substantial scope for dairy development.